DEVELOPMENT OF PAI MATERIALS BASED ON QUIPER SCHOOL APPLICATION TO IMPROVE STUDENTS' LEARNING OUTCOMES MADRASAH ALIYAH YASPIB 1 BITUNG - Nurhayati; Wadan Y. Anuli2; Abrari Ilham (RADJA PUBLIKA, 2024)
This research aims to reveal the stages in developing school based on learning materials quipper effective for studying the subject of Islamic religious education. The material developed has the following characteristics: it is online, and includes a variety of media components, namely text, images, sound, and video, which is inputted through the application quipper school, from the aspect of learning, materials, and media, and the percentage of students who achieve mastery learned after using this learning media. This research is a research and development. The development of these materials is done through five stages consists of analysis, design, production, testing, and distribution. The analysis phase includes the analysis of the purpose of making and shape the product manufacture. The design phase includes procedures for inputting text material in the form pdf / powerpoint, instructional videos shaped material, exam, homework (PR). The production stage includes the income of all the ingredients are there, synchronization and test the flow of the program. Test phase consists of a limited due diligence review by subject matter experts and media specialists, and field tests that include: preliminary field testing, playing field testing, and operational field testing. The distribution stages disseminate the revised product to the user. Data were collected using observation sheets, questionnaires and tests, and analyzed with descriptive statistics. The trial results are used to improve school quipper based on learning materials development results. The results of expert validation Morals Aqeedah material shows that the material quality is good, with a score of 3.69. Likewise, media experts assess media quality is very good, with a score of 4.65. The trial results showed that the students' ratings of the quality of materials are well developed. Aspects of learning had a mean score of 4.51 (very good), the material aspects of 4.55 (very good) and media aspects of 4.77 (very good). The mean overall score of 4.61 that is included in the criteria very well. Total percentage of students who achieve mastery learning (minimum value